The Theory of Planned Behavior Influences Online Shopping Behavior - Sutisna, Felix; Handra, Tessa (APTISI Transactions on Management (ATM), 2022)
Nowdays many factors influence shopper interested in buying merchandise through e-business, such as promotions made by e-business companies, speed and less time, fast payment transactions and low cost, and marketing mix. Most shopper utilize e-business to shop for food products, electronics, logistic (such as gojek/grab/uber, travel) and others. The application of e-business can not be separated from the expertise and knowledge of the public in using the internet and computer systems. However, Indonesian people's awareness of e-business is still low, many people do not know how to utilize it. This is due to low internet infrastructure factors, poor telecommunication facilities. This is still a barrier to the interest of the people of Indonesia to testify online. In addition, shopper confidence and trust in the security of e-business can affect someone to shop online. In explaining the factors that impact on shopper conduct to utilize e-business utilized theory of planned behavior approach. The theory of Planned Behavior (TPB) has supported the prediction of many different conducts of people. TPB shows that determining conduct is one's purpose. This study aims to analyze the impact of perceived behavioral control, subjective norm, and attitude, on purpose to shop online and its impact on online shopping behavior. Exogenous variable research is perceived behavioral control, subjective norm, and attitude. The variables of endogenous research are intended to shop online and online shopping behavior. The research sample of 100 respondents was shopper who shopped in e-business X. Data collection method using questionnaires. Data analysis method using SEM PLS.